2006
DOI: 10.5713/ajas.2006.938
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Magra Sheep from India Using Microsatellite Analysis

Abstract: Genetic diversity of Magra -a lustrous carpet wool breed of India, was investigated by means of 25 ovine microsatellite markers proposed by the Food and Agriculture Organization and the International Society for Animal Genetics (FAO-ISAG). All used microsatellites amplified well and exhibited polymorphisms. A wide range of genetic variability was observed as allele number from 3 (BM6506, OarCP20) to 10 (CSSM31), observed heterozygosity from 0.200 (BM6506) to 0.947 (OarHH35), expected heterozygosity from 0.368 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
29
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 16 publications
11
29
2
Order By: Relevance
“…However, a higher number of alleles for each locus showed that all the markers used were appropriate to analyze diversity in studied breeds. The level of variation depicted by number of alleles at each locus was similar to earlier reports on sheep breeds (Arora and Bhatia, 2006;Jakaria et al, 2012;Hepsibha et al, 2013;Crispim et al, 2014). Among the types, the mean of PIC ranged from 0.72 in LRB-PAK to 0.88 in ARB, and Shannon information index ranged from 1.58 in KER-PAK to 2.27 in ARB.…”
Section: Discussionsupporting
confidence: 72%
“…However, a higher number of alleles for each locus showed that all the markers used were appropriate to analyze diversity in studied breeds. The level of variation depicted by number of alleles at each locus was similar to earlier reports on sheep breeds (Arora and Bhatia, 2006;Jakaria et al, 2012;Hepsibha et al, 2013;Crispim et al, 2014). Among the types, the mean of PIC ranged from 0.72 in LRB-PAK to 0.88 in ARB, and Shannon information index ranged from 1.58 in KER-PAK to 2.27 in ARB.…”
Section: Discussionsupporting
confidence: 72%
“…In the present study all markers were highly informative (PIC>0.5; Arora et al, 2006). These observations suggested the additional utility of these markers for population assignment (Arora et al, 2010) in indigenous sheep and gene mapping (Kayang et al, 2002).…”
Section: Discussionmentioning
confidence: 57%
“…Microsatellites have been widely used to characterize sheep breeds of several countries (Baumung et al 2006;Peter et al 2007;Cinkulov et al 2008;Legaz et al 2008;Dalvit et al 2008;Alvarez et al 2009). Microsatellite analysis of the Nali, Chokla , Marwari (Singh et al 2007) and Magra (Arora and Bhatia 2006) breeds has been reported previously based on genotyping by silver staining methods, but a comparative study of all six breeds has not yet been described. Their unique characteristics and dwindling numbers make an analysis of their genetic diversity and relationships urgent.…”
Section: Introductionmentioning
confidence: 95%